2020
DOI: 10.1101/2020.03.23.000257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A microscopy-based kinetic analysis of yeast vacuolar protein sorting

Abstract: The yeast Saccharomyces cerevisiae is amenable to studying membrane traffic by live-cell 1 fluorescence microscopy. We used this system to explore two aspects of cargo protein traffic 2 through prevacuolar endosome (PVE) compartments to the vacuole. First, at what point during 3Golgi maturation does a biosynthetic vacuolar cargo depart from the maturing cisternae? To 4 address this question, we modified a regulatable fluorescent secretory cargo by adding a vacuolar 5 targeting signal. Traffic of the vacuolar c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…When the cells instead expressed ESCargo containing the APV tripeptide, punctate red fluorescence was observed, but for most of the cells, the fluorescence pattern showed little change upon SLF addition (data not shown). This effect highlights a limitation of ESCargo: as previously documented for yeast cells, there is a kinetic competition between aggregation in the ER and signal-dependent ER export Casler and Glick, 2020). In mammalian cells, ER export tends to win the race, and so much of the ESCargo accumulates in post-ER compartments.…”
Section: Escargo Undergoes Signal-dependent Er Export In Cultured Mammentioning
confidence: 61%
See 3 more Smart Citations
“…When the cells instead expressed ESCargo containing the APV tripeptide, punctate red fluorescence was observed, but for most of the cells, the fluorescence pattern showed little change upon SLF addition (data not shown). This effect highlights a limitation of ESCargo: as previously documented for yeast cells, there is a kinetic competition between aggregation in the ER and signal-dependent ER export Casler and Glick, 2020). In mammalian cells, ER export tends to win the race, and so much of the ESCargo accumulates in post-ER compartments.…”
Section: Escargo Undergoes Signal-dependent Er Export In Cultured Mammentioning
confidence: 61%
“…The ESCargo method has two limitations. First, when ESCargo molecules containing the APV tripeptide enter the ER, they experience a kinetic competition between aggregation and signal-dependent ER export Casler and Glick, 2020). As a result, a substantial fraction of the newly synthesized ESCargo molecules are either secreted or delivered to post-ER compartments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the final step, late endosomes fuse with the highly acidic vacuoles that contain proteases for degradation of the endosomal contents. Here very elegant experiments using an engineered fluorescent vacuolar cargo and 4D microscopy have suggested that transfer of material from PVE compartments to the vacuole most likely involves "kiss-and-run" fusion events [82,84].…”
Section: The Yeast Endosome Systemmentioning
confidence: 99%